Rift Valley Fever in Rwanda Is Urging for Enhancing Global Health Security Through Multisectoral One Health Strategy - Claude Mambo Muvunyi; Jean Claude Semuto Ngabonziza; Emmanuel Edwar Siddig; Ayman Ahmed (Microorganisms, 2025)
Rift Valley fever (RVF) is a devastating zoonotic mosquito-borne viral hemorrhagic fever disease that threats human and animal health and biodiversity in Africa, including in Rwanda. RVF is increasingly outbreaking in Africa, leading to devastating impacts on health, socioeconomic stability and growth, and food insecurity in the region, particularly among livestock-dependent communi-ties. This systematic review synthesizes existing evidence on RVF’s epidemiology, transmission dynamics, and the prevention and control measures implemented in Rwanda. Our findings high-light the rapidly increasing prevalence of RVF and the expansion of its geographical distribution and host range in Rwanda. Furthermore, the review reveals gaps in local evidence, including the existence of competent vectors of RVFV and the risk factors associated with the emergence and spread of RVF in the country. This underscores the urgent need for prospective research to inform evidence-based health policymaking, strategic planning, and the development and implementation of cost-effective preventive and control measures, including diagnosis and surveillance for early detection and response. It also calls for the institutionalization of a cost-effective, multisectoral, and transdisciplinary One Health strategy for reducing the burden and risk of climate climate-sensitive and zoonotic diseases, including RVF, in the country. We recommend exploring cost-effective human and/or animal vaccination mechanisms for RVF, integrating AI-powered drones into dis-ease vectors surveillance and control, and the routine implementation of genomics-enhanced xenosurveillance to monitor changes in pathogens and vectors dynamics in order to inform poli-cymaking and guide the control interventions.